(untitled) (Journal of the Bangladesh Agricultural University, 2024)
Cauliflower, scientifically known as Brassica oleracea var. botrytis L., is a highly adaptable vegetable that offers significant nutritional advantages and is cultivated to a varying extent in the Barishal region. An experiment was conducted in Banaripara Upazila, Barishal district, to inspect the selection of a suitable intercrop for cauliflower, with the goal of maximizing the usage of Sorjan bed space and increasing economic benefits for farmers. The study covered two consecutive years, specifically 2021-2022 and 2022-2023. The study included a combination of intercropping treatments, namely Cauliflower as sole crop (T1), Cauliflower + Red amaranth (T2), Cauliflower + coriander leaf (T3), Cauliflower + lettuce (T4), Cauliflower + radish leaf (T5) and Cauliflower + spinach (T6). A randomized complete block design with three replications was used to carry out the study, with treatment effects observed in 3×2.4 m2 of land units. The cauliflower seeds were sown on a nursery bed at October 30th, 2021, and October 29th, 2022. Twenty days older seedlings were undertaken a hardening process for a duration of 2 days. To ensure proper growth, the cauliflower crop received nutrients including N, P, K, S, Zn, B and cow dung at rates of 120, 60, 100, 24, 3.6, 2.1 kg and 3 tons per hectare, respectively. Spanning two consecutive years, the combination of cauliflower and coriander leaf provided the highest land equivalent ratio, with values of 1.68 and 1.62, respectively. Besides, in view of BCR, cauliflower intercropped with spinach resulted the highest BCR values of 1.61 in the first year and 1.50 in the second year. Cauliflower + spinach intercropping system resulted in net returns of 217,410 and 183,950 BDT, respectively. Therefore, it can be suggested that farmers can cultivate their land with a combination of cauliflower and spinach in the interest of maximizing profitability in Sorjan bed cultivation. J Bangladesh Agril Univ 22(2):166-177, 2024